Evaluating linkage to care for hypertension after community‐based screening in rural Uganda. Issue 4 (3rd February 2014) - Kotwani, Prashant; Balzer, Laura; Kwarisiima, Dalsone; Clark, Tamara D.; Kabami, Jane; Byonanebye, Dathan; Bainomujuni, Bob; Black, Douglas; Chamie, Gabriel; Jain, Vivek; Thirumurthy, Harsha; Kamya, Moses R.; et al.
Abstract Objectives To determine the frequency and predictors of hypertension linkage to care after implementation of a linkage intervention in rural Uganda. Methods During a multidisease screening campaign for HIV, diabetes and hypertension in rural Uganda, hypertensive adults received education, appointment to a local health facility and travel voucher. We measured frequency and predictors of linkage to care, defined as visiting any health facility for hypertension management within 6 months. Predictors of linkage to care were calculated using collaborative‐targeted maximum likelihood estimation (C‐TMLE). Participants not linking were interviewed using a standardised instrument to determine barriers to care. Results Over 5 days, 2252 adults were screened for hypertension and 214 hypertensive adults received a linkage intervention for further management. Of these, 178 (83%) linked to care within 6 months (median = 22 days). Independent predictors of successful linkage included older age, female gender, higher education, manual employment, tobacco use, alcohol consumption, hypertension family history and referral to local vs. regional health centre. Barriers for patients who did not see care included expensive transport (59%) and feeling well (59%). Conclusions A community health campaign that offered hypertension screening, education, referral appointment and travel voucher achieved excellent linkage to care (83%). Young adults, men and persons with low levels of formal education were among those least likely to seek care.